Análise quantitativa e econômica do tratamento de sementes para o controle da antracnose em soja - Gontijo, Guilherme Foschetti (2022)
The application of fungicides on seeds and on developing plants in fields is currently a management strategy widely used in soybean, aiming to combat diseases that can cause significant losses to this crop. Despite the proven effectiveness in disease control, the use of chemical pesticides can result in negative consequences for the environment, in addition to increasing the cost of crop production, making it desirable to reduce the amount of products used in the field. This study aimed to evaluate the effectiveness of chemical seed treatment in combination with post-planting applications of fungicides as a viable alternative for the control of Colletotrichum truncatum associated with seeds, aiming to reduce the unnecessary use of fungicide sprays on soybean in the field. For the test, eight treatments were used, all composed of seeds contaminated with C. truncatum, in a 2 x 4 scheme (2 seed treatments and 4 sprays). The experiment was carried out until the time of harvest, evaluating stands, height and weight of plants, number of pods, weight of one thousand grains, grain yield, disease index, health of harvested seeds and economic viability of the system. The chemical treatment of seeds was effective in reducing the incidence of C. truncatum in soybean seeds and provided an increase in the values of stands, plant height and weight, and grain yield, causing a decrease in the disease/damage index and in the pathogen incidence in harvested seeds. Seed treatment resulted in higher revenue for the evaluated systems, proving to be an economical and effective alternative to a greater number of fungicide sprays on plants in the field.